0301 Interaction Between the Progression of Alzheimer's Dementia and Circadian Disturbances: A 13-Year Longitudinal Study in Community-Based Older Adults. (12th April 2019) - Li, Peng; Fan, Wenqing; Yu, Lei; Lim, Andrew S P; Buchman, Aron S; Bennett, David A; Hu, Kun
Abstract: Introduction: Altered circadian rhythms occur in Alzheimer's disease (AD) even at its preclinical stage. No study to date has examined changes in circadian rhythms in parallel with AD progression longitudinally. Here we examined deterioration of daily/circadian activity rhythms as older adults progressed from no cognitive impairment (NCI), to mild cognitive impairment (MCI), and to Alzheimer's dementia. Methods: We studied 1, 032 older adults (female: 780; age: 80.8±7.4 [SD]) in the Rush Memory and Aging Project who have been followed for up to 13 years. Motor activities of ~10 days were recorded annually and were used to quantify the interdaily stability (IS) and intradaily variability (IV) of the daily/circadian activity rhythms. Cognitive assessments and clinical diagnoses were administered annually to render a clinical diagnostic classification of NCI, MCI, or Alzheimer's dementia based on the NINCDS/ADRDDA criteria. To examine how IS and IV change longitudinally with the progression of Alzheimer's dementia, we performed linear mixed-effects models with 2 change points anchored at the diagnoses of MCI and Alzheimer's dementia while adjusted for age, sex, and education. Results: Among older adults with NCI, IS showed an annual decrease of 0.008±0.001 (SE) (p<0.0001) and IV had an annual increase of 0.010±0.001 (p<0.0001). After MCI diagnosis, IS decreased ~90% faster (additional annual decrease: 0.007±0.001; p<0.0001) and IV increased ~120% faster (additional annual increase: 0.012±0.003; p<0.0001). After the diagnosis of Alzheimer's dementia, the changes in IS and IV were further accelerated with the rates of changing further increased by 0.015±0.006 for IS (twice the rate at MCI; p=0.01) and 0.052±0.009 for IV (3.4 times of the rate at MCI, p<0.0001), respectively. Conclusion: As people age, daily activity rhythms became less stable and more fragmented. The progression of Alzheimer's dementia accelerates the rhythmic degradation, suggesting that circadian disturbance may be an integral part of the process of Alzheimer's disease. Support (If Any): This work was supported by NIH grants R01AG048108, RF1AG059867, R01AG017917, and R01NS078009.